Paolo Giovio epistolografo: edizione commentata della corrispondenza con Alessandro Farnese - Fantacci, Michela; Perrelli, Raffaele; Figorilli, Maria Cristina; Ruggiero, Raffele (Università della Calabria, 2022)
The study aims to reorganize the materials that constitute the corpus of Paolo Giovio's epistolary and to re-evaluate them critically as a whole, in order to update and integrate the results of the valuable, but dated, twentieth-century edition revised by Giuseppe Guido Ferrero. On one hand, the purpose is to provide an up-to-date overview of Giovio's epistolary experience, and on the other, to analyse the extremely dense network of relationships that Giovio established during the course of his career with personalities considered central in the 16th century, thus, making a contribution to studies on the Italian Renaissance. Given the obvious need for a new critical and annotated edition, which takes into account a renewed census of the documents, but also the amount of research carried out over more than fifty years, the present research is intended as a preparation for this impressive work. It attempts to bring order to the intricate mass of information that is essential for its preparation and to clarify the situation of the materials that will be involved. While remaining within this broader perspective, the research pays particular attention to the relations between Giovio and the Roman environment under the pontificate of Paolo III Farnese, with the aim of deepening the analysis of a period still rarely treated by Giovio's critics. In this context, the historians privileged the relationship with Alessandro Farnese: the first appendix of the study contains an annotated edition of the correspondence with the young cardinal, covering the period 1536-1552. The long-lasting sodality, testified only by the consistency of Giovio's correspondence in an almost total dispersion of Farnese's responses, counts a total of 64 letters, mostly preserved in the Archivio di Stato of Parma in their original form.
Dottorato di ricerca internazionale in Studi umanistici: Testi, saperi, pratiche: dall'antichità classica alla contemporaneità, Ciclo XXXIV, a.a. 2021-2022
Keywords: Epistolography; Paolo Giovio; Renaissance; Alessandro Farnese; Rome